CONCURRENT VALIDITY OF THE CONTINUOUS SCALE-PHYSICAL FUNCTIONAL PEFORMANCE-10 (CS-PFP-10) TEST IN TRANSFEMORAL AMPUTEES - Highsmith, M. Jason (Technol Innov, 2016)
The Continuous Scale-Physical Functional Performance-10 (CS-PFP-10) test consists of 10 standardized daily living tasks that evaluate overall physical functional performance and performance in five individual functional domains: upper body strength (UBS), upper body flexibility (UBF), lower body strength (LBS), balance and coordination (BAL), and endurance (END). This study sought to determine the concurrent validity of the CS-PFP-10 test and its functional domains that involve the lower extremities (LBS, BAL, or END) in comparison to measures that have established validity for use in persons with transfemoral amputation (TFA). Ten TFA patients functioning at K3 or higher (Medicare Functional Classification Level) completed the study. Participants were assessed performing the CS-PFP-10, Amputee Mobility Predictor (AMP), 75 m self-selected walking speed (75 m SSWS) test, timed down stair walking (DN stair time), and the limits of stability (LOS) balance test. Concurrent validity was assessed using correlation analysis. The AMP, 75 m SSWS, LOS, and the DN stair time tests were strongly correlated (r = ± 0.76 to 0.86) with their paired CS-PFP-10 domain score (LBS, BAL, or END) and CS-PFP-10 total score. These findings indicate that the lower limb and balance domains of the CS-PFP-10 are valid measures to assess the physical functional performance of TFA patients.